Introduction to clinical psychology bridging science and practice - Bernstein, Douglas A. 1942-; Teachman, Bethany A. ca. 20./21. Jh; Olatunji, Bunmi O.; Lilienfeld, Scott O. 1960-2020 (Cambridge University Press, 2021)
Thoroughly updated and revised, the ninth edition of this bestselling textbook introduces students to clinical psychology as a bridge between science and practice. Extensive revisions since the previous edition have resulted in the most accessible, up-to-date and thematically integrated edition of Introduction to Clinical Psychology yet, while maintaining the authority and accessibility students and instructors have come to rely on. Updates include: three new co-authors who are internationally recognized scholar-practitioners; illustrations of how psychologists use evidence-based practices to help clients; the fictional 'Jackson family' case studies, providing vivid examples of a family confronting numerous mental health challenges; 'Thinking Scientifically' sections in each chapter, which break down how students can think critically with conflicting findings and use them to draw conclusions; 'In Review' tables at the end of each major section prompting students to review the material and test their comprehension; and an expanded image program, printed in color for the first time